Paciente femenino de 80 años de edad con enfermedad pulmonar obstructiva crónica. - Alvarado Valencia, Andrea Carolina (2021)
This present clinical case study is focused on the health status of an 80-year-old patient with chronic obstructive pulmonary disease with a history of arterial hypertension in which she was taken to a local doctor for presenting dyspnea, wheezing events, progressive cough, medium and low rib retractions; The patient reports that he has never smoked but has cooked all his life with firewood, tests are carried out which results in a diagnosis of Chronic Obstructive Pulmonary Disease (COPD). Chronic obstructive pulmonary disease is characterized by the presence of persistent respiratory symptoms and chronic airflow limitation, caused by alterations in the airway or alveoli. The main cause of COPD is smoking, exposure to wood smoke, gases, and burning of fuels for cooking and heating poorly ventilated homes. COPD is currently one of the leading causes of morbidity and mortality worldwide. The World Health Organization (WHO) anticipates a large increase in mortality in patients with COPD, which is the third cause of death in the world in 2020. The main objective of our clinical case is to identify the clinical manifestations of COPD in the patient and administer appropriate treatment.